2010
DOI: 10.1007/s10802-010-9405-2
|View full text |Cite
|
Sign up to set email alerts
|

Explicit- and Implicit Bullying Attitudes in Relation to Bullying Behavior

Abstract: The main aim of this study was to examine whether an assessment of implicit bullying attitudes could add to the prediction of bullying behavior after controlling for explicit bullying attitudes. Primary school children (112 boys and 125 girls, M age=11 years, 5 months) completed two newly developed measures of implicit bullying attitudes (a general Implicit Association Test on bullying and a movie-primed specific IAT on bullying), an explicit bullying attitude measure, and self reported, peer reported, and tea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
38
0
2

Year Published

2014
2014
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 57 publications
(42 citation statements)
references
References 57 publications
1
38
0
2
Order By: Relevance
“…Seemingly, Dijkstra et al (2008) found that the associations between bullying and peer rejection (positive) and peer acceptance (negative) were weakened when the perpetrator of bullying behavior was highly popular. These differences may be due to attributional biases and also to peer beliefs regarding these behaviors (Lansu et al 2013;van Goethem et al, 2010). These studies suggest that, although both aggression and bullying are associated with popularity, they seem to imply different interpersonal configurations that become clearer when considering the associations of aggression and bullying with social preference as a distinct dimension of social status that refers to likeability (Cillessen & Mayeux, 2004;Rose et al, 2004).…”
Section: Distinguishing Aggression and Bullying As Status Correlatesmentioning
confidence: 80%
See 1 more Smart Citation
“…Seemingly, Dijkstra et al (2008) found that the associations between bullying and peer rejection (positive) and peer acceptance (negative) were weakened when the perpetrator of bullying behavior was highly popular. These differences may be due to attributional biases and also to peer beliefs regarding these behaviors (Lansu et al 2013;van Goethem et al, 2010). These studies suggest that, although both aggression and bullying are associated with popularity, they seem to imply different interpersonal configurations that become clearer when considering the associations of aggression and bullying with social preference as a distinct dimension of social status that refers to likeability (Cillessen & Mayeux, 2004;Rose et al, 2004).…”
Section: Distinguishing Aggression and Bullying As Status Correlatesmentioning
confidence: 80%
“…However, peer influence might not be exclusively related to behavioral patterns, but also to beliefs about aggression and bullying (Burton et al 2013;Huesmann & Guerra 1997;Salmivalli & Voeten, 2004;Van Goethem et al 2010). Huesmann and Guerra (1997) defined normative beliefs as the cognitions regarding the acceptability or unacceptability of certain behaviors, considering also emotional reactions.…”
Section: Adolescent Social Norms and Beliefs: Setting The Stage Of Whmentioning
confidence: 99%
“…Boivin, Dodge y Coie (1995) mostraron que aquellas conductas que se asocian a estatus social son específicas a cada grupo en el cual son desplegadas; así, lo funcional de dichas conductas depende del grado en que estas son validadas y reforzadas en dicho contexto. En este sentido, distintos estudios muestran cómo las actitudes predicen la presencia de variadas conductas, entre ellas, conductas agresivas (Salmivalli & Voeten, 2004;van Goethem, Scholte & Wiers, 2010) y prosociales (McMahon et al, 2013). Las actitudes pueden definirse como evaluaciones estables respecto de una persona, grupo o tema, que involucran aspectos conductuales, emocionales y cognitivos (Ajzen & Fishbein, 2005;van Goethem et al, 2010).…”
Section: Creencias Normativasunclassified
“…Implicit attitudes, linked to the reward center of the brain, have been found to differentially influence and predict adolescent behavior (van Goethem, Scholte, & Wiers, 2010). While an adolescent can clearly articulate an explicit behavioral intention or plan to engage in or abstain from a specific sexual behavior, he may simultaneously have a conflicting, implicit willingness or openness to engage in that behavior (Gibbons, Gerrard, Reimer, & Pomery, 2006).…”
Section: Willingness Vs Intentionsmentioning
confidence: 99%